Alternative housing models for precariously housed older Australians - Tually, S.; Coram, V.; Faulkner, D.; Barrie, H.; Sharam, A.; James, Amity; Lowies, B.; Bevin, K.; Webb, Eileen; Hodgson, Helen; Cebulla, A. (2022)
AHURI is a national independent research network with an expert not-for-profit research management company, AHURI Limited, at its centre. AHURI’s mission is to deliver high quality research that influences policy development and practice change to improve the housing and urban environments of all Australians. Using high quality, independent evidence and through active, managed engagement, AHURI works to inform the policies and practices of governments and the housing and urban development industries, and stimulate debate in the broader Australian community. AHURI undertakes evidence-based policy development on a range of priority policy topics that are of interest to our audience groups, including housing and labour markets, urban growth and renewal, planning and infrastructure development, housing supply and affordability, homelessness, economic productivity, and social cohesion and wellbeing.